Association of IL-10 and IL-10RA single nucleotide polymorphisms with the responsiveness to HBV vaccination in Chinese infants of HBsAg(+)/HBeAg(−) mothers: a nested case–control study. Issue 11 (28th November 2018) - Wen, Simin; Wu, Yanhua; Pan, Yuchen; Cao, Mengzhuo; Zhao, Dan; Wang, Chong; Wang, Chuan; Kong, Fei; Li, Jie; Niu, Junqi; Jiang, Jing
Abstract : Objectives: To investigate the association of interleukin (IL)-10 and IL-10 receptor A (IL-10RA) single nucleotide polymorphisms with the responsiveness to hepatitis B virus (HBV) vaccination in newborns whose mothers were hepatitis B surface antigen (HBsAg)(+)/hepatitis B e antigen (HBeAg)(–). Design: Nested case–control study. Setting: Changchun, China. Participants: 713 infants from a Han Chinese population whose mothers were HBsAg(+)/HBeAg(–) and participated in the prevention of mother-to-child transmission of HBV at the First Hospital of Jilin University from July 2012 to July 2015 were included. Infants were excluded for HBsAg-positive; unstandardised vaccination process; inadequate blood samples; not Han Chinese and failed genotyping. Results: Infants with artificial feeding pattern were correlated with low responsiveness to HBV vaccination (p=0.009). The GG genotype of IL-10 rs3021094 was correlated with a higher risk of low responsiveness to HBV vaccination (OR 2.80, 95% CI 1.35 to 5.83). No haplotype was found to be correlated with responsiveness to HBV vaccination. No gene–gene interaction was found between IL-10 and IL-10RA. Conclusions: Our study found that IL-10 gene variants were significantly associated with the immune response to the HBV vaccine. Identifying these high-risk infants who born to HBsAg(+)/HBeAg(–) mothers and low responses to hepatitis B vaccination will provide evidence for individualised prevention strategies.